2007
DOI: 10.1002/ajmg.b.30538
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of cognitive functions in families with bipolar disorder

Abstract: Bipolar disorder is highly heritable. Cognitive dysfunctions often observed in bipolar patients and their unaffected relatives implicate that these impairments may be associated with genetic predisposition to bipolar disorder and thus fulfill the criteria of a valid endophenotype for the disorder. However, the most fundamental criterion, their heritability, has not been directly studied in any bipolar population. This population-based study estimated the heritability of cognitive functions in bipolar disorder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
(69 reference statements)
1
30
0
Order By: Relevance
“…However, literature so far has been inconsistent on the type of cognitive tasks that are impaired in relatives, with some studies revealing deficits in executive functioning as well as response-inhibition (Antila et al, 2007; Zalla et al, 2004), while other studies suggest a deficit in response inhibition only (Frangou et al, 2005). A meta-analysis for 18 cognitive variables between relatives, patients and healthy controls reported mixed results (Bora et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, literature so far has been inconsistent on the type of cognitive tasks that are impaired in relatives, with some studies revealing deficits in executive functioning as well as response-inhibition (Antila et al, 2007; Zalla et al, 2004), while other studies suggest a deficit in response inhibition only (Frangou et al, 2005). A meta-analysis for 18 cognitive variables between relatives, patients and healthy controls reported mixed results (Bora et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they should be state-independent traits present in illness as well as in remission, and they should be more frequent in unaffected relatives of patients than in general population 4 . The endophenotype criterion of heritability has been met for certain neurocognitive functions in a study of a population-based Finnish sample of 110 individuals from 52 families with bipolar disorder who were administered a comprehensive test battery 51 . The results indicated high heritability of executive functions and psychomotor processing speed, but not of verbal learning.…”
Section: Searching For Cognitive Endophenothypes: Family Studies Of Bmentioning
confidence: 99%
“…The role of slowed processing speed in verbal memory has been evidenced in other mental disorders including schizophrenia [9][10][11] and depression [12] and also in a twin sample of bipolar I disorder patients [13] . According to our previous studies of bipolar I disorder patients and their first-degree relatives, processing speed may be a potential endophenotype [14] for bipolar disorder [4,15] . In our previous study, we found that both the patients with familial bipolar I disorder and their unaffected first-degree relatives were significantly impaired compared to the controls in the task measuring processing speed (assessed with the digit symbol subtest of the Wechsler Adult Intelligence Scale-Revised, WAIS-R) [4] .…”
Section: Introductionmentioning
confidence: 96%